2011
DOI: 10.2304/rcie.2011.6.4.383
|View full text |Cite
|
Sign up to set email alerts
|

Agency and Advocacy: Disabled Students in Higher Education in Ghana and Tanzania

Abstract: Between 10% and 15% of the world's population are thought to be disabled. The 2006 United Nations Convention on the Rights of Persons with Disabilities is an example of emerging global policy architecture for human rights for disabled people. Article 24 states that disabled people should receive the support required to facilitate their effective education. In research, links between higher education access, equalities and disability are being explored by scholars of the sociology of higher education. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 35 publications
2
23
0
3
Order By: Relevance
“…25 These challenges extend across educational levels as Sub-Saharan universities rarely consider admitting students with disabilities to specific programs of their choice. 26 Unfortunately, the current study did not directly assess the highest level of education successfully completed. However, our finding that a relatively high proportion of participants with significant disabilities reported having spent more years in school may be an indirect indicator of limitations in the local school environment’s ability to adapt and provide effective accommodations for students with disabilities.…”
Section: Discussionmentioning
confidence: 94%
“…25 These challenges extend across educational levels as Sub-Saharan universities rarely consider admitting students with disabilities to specific programs of their choice. 26 Unfortunately, the current study did not directly assess the highest level of education successfully completed. However, our finding that a relatively high proportion of participants with significant disabilities reported having spent more years in school may be an indirect indicator of limitations in the local school environment’s ability to adapt and provide effective accommodations for students with disabilities.…”
Section: Discussionmentioning
confidence: 94%
“…Interactionist perspectives put relatively more emphasis on the direct effects of impairment than is found in most interpretations of the social model and also foreground the diverse and fluctuating nature of disabled people's experiences (Ghai, 2002;Lang, 2007;Shakespeare, 2009). Both the social and the interactionist model of disability, however, leave space for society to counter the severe economic and other disadvantages often associated with impairment, for example, through actively including disabled children in education (Morley & Croft, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Research focusing on disabled students by Morley and Croft (2011) found that, while disability was associated with constraints, such as misrecognition, exclusion and even danger, students' participation and achievement in higher education offered opportunities for transforming their identities. Although overall students' experiences of higher education were positive (e.g.…”
Section: Participation In and Quality Of Higher Educationmentioning
confidence: 99%
“…the student 'status' was empowering and supportive staff, friendships and networks created an enabling environment), students also reported that classes were large, teaching was of low quality, there was favouritism and corruption and facilities and resources were lacking (Morley, 2010). In both Ghana and Tanzania, there was evidence of sexual harassment and sex for grades, and a lack of support for disabled students (Morley, 2010;Morley and Croft, 2011). At the policy level, Morley found that widening participation initiatives were under-funded and monitoring and evaluation was uneven and unsystematic, focusing narrowly on gender.…”
Section: Participation In and Quality Of Higher Educationmentioning
confidence: 99%
See 1 more Smart Citation